The strategy of economic planning : a case study of Pakistan - Haq, Mahbub ul (Karachi : Pakistan Branch, Oxford University Press, 1966)
A case study of Pakistani approach to economic planning, rationale for planning decisions, model for regional planning and evaluation of a five year plan.
On verso of t.p.: Second impression, with new preface.
Includes bibliographical references and index.
sju 25/01/2019
Loans
Keywords: Pakistan